2021
DOI: 10.1029/2021jd034811
|View full text |Cite
|
Sign up to set email alerts
|

Sources, Occurrence and Characteristics of Fluorescent Biological Aerosol Particles Measured Over the Pristine Southern Ocean

Abstract: In this study, we investigate the occurrence of primary biological aerosol particles (PBAP) over all sectors of the Southern Ocean (SO) based on a 90‐day data set collected during the Antarctic Circumnavigation Expedition (ACE) in austral summer 2016–2017. Super‐micrometer PBAP (1–16 µm diameter) were measured by a wide band integrated bioaerosol sensor (WIBS‐4). Low (3σ) and high (9σ) fluorescence thresholds are used to obtain statistics on fluorescent and hyper‐fluorescent PBAP, respectively. Our focus is on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 82 publications
(113 reference statements)
8
6
0
Order By: Relevance
“…Furthermore, the corresponding size distribution is centered at 5 ± 2 μm which is similar to the size of bacteria agglomerates previously identified in both ambient coastal aerosol 51 and nascent SSA generated in laboratory experiments. 18,30 Interestingly, a number of recent studies suggest that PBAP constitutes only a small portion of the FP over or close to marine environments 27,49 and our data would appear to corroborate this: the PBAP contribution to the total FP was only 0.46% (0.04% of all CP).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the corresponding size distribution is centered at 5 ± 2 μm which is similar to the size of bacteria agglomerates previously identified in both ambient coastal aerosol 51 and nascent SSA generated in laboratory experiments. 18,30 Interestingly, a number of recent studies suggest that PBAP constitutes only a small portion of the FP over or close to marine environments 27,49 and our data would appear to corroborate this: the PBAP contribution to the total FP was only 0.46% (0.04% of all CP).…”
Section: Resultssupporting
confidence: 86%
“…Recently, several experimental efforts were made to measure PBAP within marine environments [26][27][28] and in laboratory studies 29,30 combining UV-LIF methods with offline measurements such as lter collection. Other studies have also attempted to determine the role of seawater characteristics on the emission of PBAP.…”
Section: Introductionmentioning
confidence: 99%
“…FAPs of type A (which are typically bacterial particles (∼1 μm) as suggested by Hernandez et al (2016)) dominated the identified types throughout the cruise (Figure 3c). Dominances of FAPs of type A in the MBL have also been found in previous studies (Kawana et al, 2021;Moallemi et al, 2021). Moallemi et al (2021) revealed that FAPs concentrations in the MBL positively correlated with bacteria (∼0.5-1 μm) and small-sized eukaryotic phytoplankton (∼1-3 μm) concentrations in surface seawater of the SO.…”
Section: Average Particle Size Distributions Over the Sosupporting
confidence: 82%
“…Dominances of FAPs of type A in the MBL have also been found in previous studies (Kawana et al, 2021;Moallemi et al, 2021). Moallemi et al (2021) revealed that FAPs concentrations in the MBL positively correlated with bacteria (∼0.5-1 μm) and small-sized eukaryotic phytoplankton (∼1-3 μm) concentrations in surface seawater of the SO. A bimodal PSD and a local minimum in the submicron size range between two modes were observed throughout the cruise (Figure 3b).…”
Section: Average Particle Size Distributions Over the Sosupporting
confidence: 82%
See 1 more Smart Citation